Skyrmion pinning energetics in thin film systems - Gruber, Raphael; Zazvorka, Jakub; Brems, Maarten A.; Rodrigues, Davi R.; Dohi, Takaaki; Kerber, Nico; Seng, Boris; Vafaee, Mehran; Everschor-Sitte, Karin; Virnau, Peter; Klaeui, Mathias (Nature Communications, 2022)
A key issue for skyrmion dynamics and devices are pinning effects present in real systems. While posing a challenge for the realization of conventional skyrmionics devices, exploiting pinning effects can enable non-conventional computing approaches if the details of the pinning in real samples are quantified and understood. We demonstrate that using thermal skyrmion dynamics, we can characterize the pinning of a sample and we ascertain the spatially resolved energy landscape. To understand the mechanism of the pinning, we probe the strong skyrmion size and shape dependence of the pinning. Magnetic microscopy imaging demonstrates that in contrast to findings in previous investigations, for large skyrmions the pinning originates at the skyrmion boundary and not at its core. The boundary pinning is strongly influenced by the very complex pinning energy landscape that goes beyond the conventional effective rigid quasi-particle description. This gives rise to complex skyrmion shape distortions and allows for dynamic switching of pinning sites and flexible tuning of the pinning.
CRIS-Team Scopus Importer:2023-03-27